THE INFLUENCE OF INTERACTIVE EDUCATION ON THE PRACTICES OF CONTROLLING RISK FACTORS FOR TYPE 2 DIABETES IN ADOLESCENTS: PENGARUH EDUKASI INTERAKTIF TERHADAP PRAKTIK PENGENDALIAN FAKTOR RISIKO DIABETES MELLITUS TIPE 2 PADA REMAJA - Widagdo, Wahyu; Mariani Tambun, Yetty; Mumpuni, Mumpuni; Mutarobin, Mutarobin; Chairani, Reni (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
The prevalence of type 2 diabetes mellitus (DM) continues to increase globally, including among adolescents. This condition is influenced by risk factors such as obesity, family history, and low physical activity. Preventive efforts through interactive education are expected to improve risk factor control practices from an early age. This study used a quasi-experimental design with a two-group pretest-posttest. A sample of 60 adolescents was obtained through purposive sampling and divided into an intervention group (n=30) and a control group (n=30). The research instrument was a questionnaire on type 2 DM risk factor control practices. The intervention was carried out through six interactive education and monitoring sessions, while measurements were taken before and after the intervention. The analysis results showed a significant increase in risk factor control practices in the intervention group based on a paired t-test (p < 0.001). An independent t-test also showed a significant difference between the intervention and control groups after the intervention (p < 0.001). This study concluded that interactive education is an effective strategy to improve type 2 DM risk factor control practices in adolescents. Researchers recommend integrating interactive education into school health programs and active family involvement to strengthen efforts to prevent type 2 diabetes from adolescence.